A diverse view of science to catalyse change. Issue 34 (17th August 2020) - Urbina-Blanco, César A.; Jilani, Safia Z.; Speight, Isaiah R.; Bojdys, Michael J.; Friščić, Tomislav; Stoddart, J. Fraser; Nelson, Toby L.; Mack, James; Robinson, Renã A. S.; Waddell, Emanuel A.; Lutkenhaus, Jodie L.; Godfrey, Murrell; et al.
Abstract : Valuing diversity leads to scientific excellence, the progress of science and, most importantly, it is simply the right thing to do. We must value diversity not only in words, but also in actions. Abstract : Valuing diversity leads to scientific excellence, the progress of science and, most importantly, it is simply the right thing to do. We can value diversity not only in words, but also in actions.